Legal issues of egg donation - Cárdenas Krenz, Ronald (2014)
The article addresses the controversia[ issue of egg donation, analyzing the way it is treated under Peruvian law, national doctrine, and jurisprudence, with references to comparative law, including a review of the subject applying logic to finally issue from a legal perspective a value judgment on this practice that has been actually taking place in our country under questíonable legal interpretation.